Coronary Heart Disease Risk in Patients with Schizophrenia: A Lebanese Cross-Sectional Study. Issue 1 (2017) - Haddad, Chadia; Hallit, Souheil; Salameh, Pascale; Bou-Assi, Tarek; Zoghbi, Marouan
Background: Coronary heart disease (CHD) is a leading cause of premature death in patients with schizophrenia. CHD risk in Lebanese patients with schizophrenia remains unknown. Objectives: To (i) evaluate CHD risk of patients with schizophrenia in Lebanon; and (ii) detect the modifiable and non-modifiable factors affecting this risk. Methods: Cross-sectional study of 329 patients with schizophrenia aged 20–75 years. Ten-year hard CHD risk was calculated using the Framingham risk score. A logistic regression was conducted taking the dichotomous hard CHD (<10% and ≥10%) as the dependent variable. Results: Ten-year hard CHD risk was low (<10%) in 60.8% of patients, intermediate (10–20%) in 31.6%, and high (>20%) in 7.6%. Multivariate analysis showed that the mean 10-year hard CHD risk was 8.76±6.92 (10.82±6.83 in men and 3.18±2.90 in women). Ten-year hard CHD risk was higher in patients with the metabolic syndrome (odds ratio [OR] 2.67, confidence interval [CI] 1.54–4.64), a longer duration of schizophrenia (OR 1.03, CI 1.01–1.05), a history of other medical illnesses (OR 2.02, CI 1.18–3.47), and in those participating in art therapy (OR 2.13, CI 1.25–3.64) or therapeutic education (OR 1.93, CI 0.93–4.01). Ten-year hard CHD risk was lower in patients receiving risperidone (OR 0.23, CI 0.08–0.68), any anti-epileptic (OR 0.41, CI 0.24–0.73), or any benzodiazepine (OR 0.33, CI 0.17–0.66) medication. Conclusion: CHD is prevalent in patients with schizophrenia in Lebanon. Physicians are recommended to monitor the components of the metabolic syndrome to identify patients with increased risk of cardiovascular diseases.